The Effect of Moringa Leaf Flour Addition in Steamed Sponge Cake Made from a Mixture of Wheat and Banana Flours - Indah Sari, Fenny; Hotnida Sinaga; Linda Masniary Lubis (Talenta Publisher, 2019)
The aim of this study was to determine the suitable Moringa oleifera leaf added for steamed sponge production, which was made from the mixture of wheat and banana flours. This research was conducted. This research was conducted by using completely randomized design with 2-factors, namely percentage of moringa leaf flour (K): (0,0% ; 1,0% ; 2,0%) and comparison of mixture wheat flour and banana flour (P): (100%:0% ; 75%:25% ; 50%:50% ; 25%:75%). The results showed that the addition of more moringa leaf flour increased the ash, protein and crude fiber contents in the composite flours. The increment might be related to higher ash, protein and fiber contents in moringa leaf flour than that of in both wheat flour and banana flour. In addition, higher banana flour substitution raised the moisture and ash contents. Meanwhile, the specific volume of cake decreased because banana flour does not have gluten. Based on the protein content and organoleptic values, the addition of 2% moringa leaf flour and the ratio of wheat flour to banana flour (75%:25%) produced the best quality of steamed sponge cake.